Development of Islamic Religious Education Based on Independent Curriculum in Madrasah Aliyah - Zubaidi, Ahmad; Saidah, Saadatus (research, training and philanthropy institution Natural Aceh, 2025)
This study analyzes the implementation of the independent curriculum in Islamic religious education and the challenges in its implementation. This study was conducted at Madrasah Aliyah Walisongo 2 Banyuanyar Probolinggo; the researcher chose this research location because it has relevance to the research topic, supports the availability of the data needed, and provides easy access and support from related parties. The approach used in this study is qualitative. The data collection technique used is interviews with one of the sources, namely the Islamic religious education teacher and the deputy head of the curriculum, using the data analysis method (descriptive), then presenting the data and drawing conclusions. The results of the study indicate that the implementation of the independent curriculum has several strategies for implementing Islamic religious education at Madrasah Aliyah Walisongo 2 Banyuanyar, including student evaluation, teacher training such as seminars, technical guidance, workshops, and MGMP activities (subject teacher deliberations), Implementing an Inclusive Learning Approach, Increasing Parental Involvement. Then, the strategic steps to solve the challenges of modern education while maintaining religious values in students' lives; the implications of this study are changes to the curriculum for Islamic religious education so that it becomes a foundation in the learning process to use contemporary methods.